Interpersonal Communication in the Digital Era: The Relationship with Self-Control Among Smartphone-Using Students at SMAN 2 Semarang - Ishma Najya Zafira Purnama; Nailul Fauziah; Elmaya Sari Pulungan (Jurnal Multidisiplin West Science, 2026)
Currently, the use of smartphones affects interpersonal communication, as individuals begin to prioritize smartphones and ignore those around them, even though interpersonal communication is very important for individual life. This study was conducted to determine the relationship between self-control and students’ interpersonal communication of smartphone users in 2 Senior High Schools in Semarang. The population in this study consisted of 256 students; 59 were selected as subjects for scale trials, and 197 were selected as the research sample using a cluster sampling technique. The instruments used are the self-control scale (21 items, α = .852) and the interpersonal communication scale (21 items, α = .836). The results of the simple regression analysis show a significance value of .000 (p < .05) and a correlation coefficient of rxy = .348. The results of the analysis indicate that the hypothesis is accepted, indicating a positive and significant relationship between self-control and interpersonal communication among smartphone-using students at SMA Negeri 2 Semarang. Self-control provides an effective contribution of 12.1%.